The nexus of community perception on turning idyllic Panchor town into a future river tourism destination - Saad, Mazni; Husin, Nor Azilah; Rosman, Siti Nur Hidayah; Husain, Rosita; Abdul Latif @ Bapoo, Lilisuriani (Taylor & Francis, 2023)
Panchor town on the Muar River would be ideal for river tourism due to its scenic beauty and peaceful atmosphere. In proposing the town as a future river tourism destination, this paper examines the relationship between residents’ perceptions of river-based tourism development and their attachment to the place, their intrinsic motivation and their knowledge of tourism. This study focuses on Panchor residents’ perceptions via a survey at a pre-tourism development stage. The data were then analyzed using SmartPLS 4. The findings indicate three factors were positively related and significantly influenced the residents’ perception of river-based tourism development with a high R-square value, indicating a more reliable and trustworthy result. The relevant authorities should consider getting the community aware of the potential benefits and sustainability of a tourism development plan through careful planning and evaluating the community’s needs and resources.